Kernel-independent fast multipole method within the framework of regularized Stokeslets. (November 2016) - Rostami, Minghao W.; Olson, Sarah D.
Abstract: The method of regularized Stokeslets (MRS) uses a radially symmetric blob function of infinite support to smooth point forces and allows for evaluation of the resulting flow field. This is a common method to study swimmers at zero Reynolds number where the Stokeslet is the fundamental solution corresponding to the kernel of the single layer potential. Simulating the collective motion of N micro-swimmers using the MRS results in at least N 2 pair-wise interactions. Efficient simulation of a large number of swimmers in free space is observed with the implementation of the kernel-independent fast multipole method (FMM) for radial basis functions. We illustrate the complexity of the algorithm on a simple test case where we study regularized point forces, showing that the method is of order N . Additionally, we explore accuracy in time for the MRS where the swimmers are modeled as Kirchhoff rods and the kernel-independent FMM is compared to the direct calculation using the standard MRS. Optimal hydrodynamic efficiency is also explored for different configurations of swimmers. Abstract : Highlights: Kernel-independent fast multipole method considered with regularized forces. Regularized solutions correspond to kernels involving radial basis functions. Hydrodynamic efficiency and swimming direction of many swimmers is investigated. Method is of order N where N is the number of point forces. O ( N )